Políticas públicas e violência infanto-juvenil na cidade de Cascavel : para além da sujeição criminal - Almeida, Thiago Nobrega de (2014)
This study seeks to analyze the treatment given by the State to Brazilian children and adolescents involved in violent crime, particularly in the city of Cascavel, located in the western of Paraná state. This city was chosen as a reference location for this work, due to the continuous increase of violence, especially in the number of homicides. The research first presents a historical retrospective of the rights guarantee system construction, through a literature review, from the fifteenth-century in Europe until the present day, focusing in Brazil, mainly the Children and Adolescents Statute, promulgated in 1990. After that, to understand the reasons for violence increase, a descriptive analysis of the variables of existing databases is made, considering national and regional levels, with particular focus on the city of Cascavel. For this, quantitative data collection technique was used, as well as an analysis of the structure and performance of the integral protection network in the city of Cascavel. Finally, after discussing the importance of public policies to prevent juvenile crime, with the participation of Public Security and civil society, there is evidence that there is still a lot to be done for children and adolescents, such as the need of integrated actions between the actors involved in the prevention and awareness of authorities and politicians of a greater contribution of public funds to areas related to the protection of children and youth.